(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
In this work, we have used the basic techniques for measuring the gamma rays by using a sodium iodide detector that is thallium activated ( ) to study the decay schemes and the energy spectrum of cobalt and sodium isotopes. We have obtained in this work: • The detector calibration and the resolution of a spectrometer. • The spectrum of cobalt and sodium isotopes. • The experimental and analytical study of the decay schemes and the energy spectrum of both isotopes Cobalt and Sodium • The comparison of energy lines of the energy spectrum with exited states of the exited nucleus and produced from cobalt and sodium . Comparing the results obtained with the results available in this field, indicates a very good agreement.